Body mass index, abdominal fatness, weight gain and the risk of urinary incontinence: a systematic review and dose–response meta‐analysis of prospective studies. (7th October 2019) - Aune, D; Mahamat‐Saleh, Y; Norat, T; Riboli, E
Abstract : Background: Adiposity has been associated with elevated risk of urinary incontinence in epidemiological studies; however, the strength of the association has differed between studies. Objectives: To conduct a systematic literature review and dose–response meta‐analysis of prospective studies on adiposity and risk of urinary incontinence. Search strategy: We searched PubMed and Embase databases up to 19 July 2017. Selection criteria: Prospective cohort studies were included. Data collection and analysis: Data were extracted by one reviewer and checked for accuracy by a second reviewer. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated using random effects models. Main results: Twenty‐four prospective studies were included. The summary RR per 5 kg/m 2 increment in body mass index (BMI) was 1.20 (95% CI 1.16–1.25, I 2 = 62%, n = 11) for population‐based studies and 1.19 (95% CI 1.08–1.30, I 2 = 87.1%, n = 8) for pregnancy‐based studies, 1.18 (95% CI 1.14–1.22, I 2 = 0%, n = 2) per 10 cm increase in waist circumference and 1.34 (95% CI 1.11–1.62, I 2 = 90%, n = 2) per 10 kg of weight gain. Although the test for nonlinearity was significant for BMI, P = 0.04, the association was approximately linear. For subtypes of urinary incontinence the summary RR per 5 BMI units was 1.45 (95% CI 1.25–1.68, I 2 = 85%, n = 3) for frequent incontinence, 1.52 (95% CI 1.37–1.68, I 2 = 34%, n = 4) for severe incontinence, 1.33 (95% CI 1.26–1.41, I 2 = 0%, n = 8) for stress incontinence, 1.26 (95% CI 1.14–1.40, I 2 = 70%, n = 7) for urge incontinence, and 1.52 (95% CI 1.36–1.69, I 2 = 0%, n = 3) for mixed incontinence. Conclusion: These results suggest excess weight may increase risk of urinary incontinence. Tweetable abstract: Overweight and obesity increase the risk of urinary incontinence. Tweetable abstract: Overweight and obesity increase the risk of urinary incontinence.